Susceptibility and compatibility of biomphalaria tenagophila from the Río de la Plata basin with schistosoma mansoni from Brazil - Borda, Carlos Edgardo (2010)
Fil: Borda, Carlos Edgardo. Universidad Nacional del Nordeste. Facultad de Medicina; Argentina.